Differences in Viewpoints Between East and West in the Evolution of MACROECONOMIC Theories - Nijar Kurnia Romdoni; Rama Nugraha Irawan S (EKOBIMA, 2023)
This article analyses studies differences in viewpoints between east and west of macro economic theories. This article also explains how the evolution of macro economics from period to period with each point of view, between East and West. Islamic Economic can be traced back to the life of Prophet Muhammad, but Islamic Economic thought began to be applied and began to grow rapidly in more than three centuries since the death of the Prophet Muhammad. While conventional economic evolution to revive after experiencing the dark age, philosopers from the West began to express their opinions about macro economics. This article also compares Keynes’ theory wich represents the West and Yusuf Al-Qardhawi’s theory wich represents the East. This article compares that two philosophers from an understanding of production and an understading of interest. The two philosophers certainly have different views both in production and interest. Next, this article argues that given the requirements of Muslim countries for direct taxes and zakat regarding personal consumption expenditures. Its introduction would assist in financing high levels of economic development. Next, mentioned that zakat can help economics problem, such as unemployment, poverty and prevent hoarding of wealth.